Assessing the adequacy of contribution rates towards employees' provident fund in Malaysia - Saidi N.A.N.; Yusuf M.M.; Basah M.Y.A. (American Institute of Physics Inc., 2024)
The vital role of Malaysian Employees' Provident Fund (EPF) is to provide financial support for its participants during retirement years. However, the issues of inadequacy have risen and EPF has been through various improvements in order to cope with current living situations, including making adjustment in the contribution rates. This study intends to provide the projection of EPF accumulations for three different types of contribution rates namely contribution rates at current fixed rate, increasing and decreasing proportion. Then, the replacement ratio is calculated and is used as an indicator to determine the adequacy of retirement income delivered by EPF. The ideal replacement ratio recommended by financial advisors is at 70%. Based on the findings in this study, contribution rates following a decreasing proportion gives replacement ratio that exceeds or nearest to the ideal replacement ratio, while contribution rates at current fixed rate gives replacement rates that fall far from 70%. Therefore, this study shows that the accumulated amount in the fund with contribution rates following a decreasing proportion gives higher replacement ratio and is recommended to be applied by the Malaysian EPF. 2017 Author(s).